Tanggung Jawab Pidana Pengurus Partai Politik sebagai Korporasi dalam Tindakan Korupsi dan Pencucian Uang - Rachmawati, Ayudya Rizqi; Manab, Abdul; Mulya, Kukuh Budi (Universitas Jember, 2024)
The progress of democracy in a country positions political parties as key actors with a central role in the political system. However, the involvement of political parties in criminal acts such as corruption and money laundering has tarnished their reputation as organizations, eroded public trust, and posed significant challenges to law enforcement. This study explores the criminal liability of political parties as corporate entities, supported by primary, secondary, and tertiary legal sources, and is conducted within a normative legal research framework. The findings indicate that there are five main perspectives to examine the political, philosophical, legal, historical, and sociological foundations of criminal law regarding corporate responsibility in cases of corruption and money laundering. The ideal approach to prosecuting political parties as corporations involves rethinking the issue of corporate crime and focusing on two distinct categories of corporations: private corporations and special or public corporations, each subject to different criminal provisions. It is necessary to reform the nature of corporations as platforms for implementing ideas by revising certain elements of anti-corruption and anti-money laundering laws related to corporate entities. Many issues concerning fines, for instance, can be addressed by enacting laws with explicit provisions for corporate sanctions. Keywords: Political Party, Corporation, Criminal Acts of Corruption, Money Laundering Crime.